Impact of accreditation on health care services performance in Kiryandongo district, Uganda: a longitudinal study - Moses Matovu; Elias Musiime; Patrick Olak; Muhammad Mulindwa; Eve Namisango; Kilian Songwe (BMC, 2022)
Abstract Background The COVID-19 pandemic has emphasised the need for quality laboratory services worldwide. There is renewed focus to strengthen country capacities and laboratories to effectively respond to public health emergencies and patient outcomes. Uganda launched the accreditation program for public health facilities in 2016 with sixteen laboratories. As of June 2021, twenty-three public laboratories have attained ISO 15189:2012 accreditation status. Despite the tremendous achievements of accrediting laboratories in Uganda, laboratory services still face challenges like stock out of commodities and limited testing scopes. We conducted this study to evaluate the impact of accreditation on health care services performance in Kiryandongo district, Uganda. Methods We conducted a longitudinal study from January 1, 2020- April 30, 2021 at ten health facilities in Kiryandongo district. We collected health care services performance data from the MoH dhis-2 on selected indicators for HIV, TB, Malaria, Laboratory, Maternal & child health and dhis-2 reporting. We used Generalized Estimating Equations to estimate the impact of accreditation on health care services performance at the different health facilities. Results The odds at the accredited facility in comparison to the non-accredited public facilities were; 14% higher for ART enrolment (OR = 1.14, 95% CI: 1.04-1.25), 9% lower for determine testing kits stock out (OR = 0.91, 95% CI: 0.85-0.97), 28% higher for TB case diagnosis (OR = 1.28, 95% CI: 1.10-1.49), 19% higher for TB case enrolment (OR = 1.19, 95% CI: 1.04-1.36), 104% higher for maternity admissions (OR = 2.04, 95% CI: 1.60-2.59), 63% higher for maternity deliveries (OR = 1.63, 95% CI: 1.39-1.90) and 17% higher for reporting hmis 10:01 data to dhis-2 (OR = 1.17, 95% CI: 1.04-1.31). The odds at the accredited facility in comparison to the non-accredited PNFP facilities were; 26% higher for ART enrolment (OR = 1.26, 95% CI: 1.17-1.36), 33% higher for TB case diagnosis (OR = 1.33, 95% CI: 1.15-1.55), 24% higher for TB case enrolment (OR = 1.24, 95% CI: 1.09-1.42), 136% higher for maternity admissions (OR = 2.36, 95% CI: 1.89-2.94), 76% higher for maternity deliveries (OR = 1.76, 95% CI: 1.51-2.04) and 2% higher for reporting of hmis-10:01 data to dhis-2 (OR = 1.02, 95% CI: 1.01-1.03). Conclusions HIV, TB, laboratory, MCH, and reporting to dhis-2 selected indicators were positively impacted by accreditation. This impact translated into increased health care services performance at the accredited facility as compared to the non-accredited facilities.